Copper sulfate and carbon tetrachloride induces a uniform response at the level of the redox system and the nature of this response depends on age - E. G. Ivanov; K. M. Lebid-Biletska; A. I. Bozhkov; Y. V. Nikitchenko (Regulatory Mechanisms in Biosystems, 2024)
The concept of oxidative stress, which is a development of D. Harman’s idea of random harmful tissue damage by free radicals, remains one of the most popular in the study of pathological processes, including age-dependent chronic changes. The work tested the hypothesis according to which, a shift in equilibrium towards pro-oxidants, i.e. oxidative stress, is the primary adaptive response of the body to exogenous toxic environmental factors. To test this, a number of indicators of the redox system were determined as a response to hepatotoxic compounds of different nature (copper sulfate and carbon tetrachloride) in young and old animals. The amount of lipid hydroperoxides and the activity of a number of antioxidant enzymes were determined in the blood serum of young (3 months) and old (20 months) rats before exposure (initial level) and after repeated sequential injections (3 injections) of copper sulfate at a dose of 1 mg/100 g body weight and carbon tetrachloride in a dose of 0.1 mL in 50% vegetable oil. It was found that in intact (initial level) old animals, the indicators of the redox system are shifted towards antioxidants. After three consecutive administrations of various hepatotoxic compounds, with an interval of 48 hours between administrations, the balance shifted towards pro-oxidants, regardless of the inducer, however, this effect was more pronounced in old animals compared to young ones, relative to their initial level. Such different reactivity of redox system indicators in animals of different ages led to the “evening out” of the initially different redox system indicators. We came to the conclusion that changing the balance in the pro-oxidant-antioxidant system is a universal, primary reaction of the body to endogenous or exogenous factors that perform regulatory functions and, depending on the temporal and functional characteristics of the body, are “transformed” into specific physiological manifestations.